DNA barcoding and the identification of tree frogs (Amphibia: Anura: Rhacophoridae). (3rd July 2016) - Dang, Ning-Xin; Sun, Feng-Hui; Lv, Yun-Yun; Zhao, Bo-Han; Wang, Ji-Chao; Murphy, Robert W.; Wang, Wen-Zhi; Li, Jia-Tang
Abstract: The DNA barcoding gene COI (cytochrome c oxidase subunit I) effectively identifies many species. Herein, we barcoded 172 individuals from 37 species belonging to nine genera in Rhacophoridae to test if the gene serves equally well to identify species of tree frogs. Phenetic neighbor joining and phylogenetic Bayesian inference were used to construct phylogenetic trees, which resolved all nine genera as monophyletic taxa except for Rhacophorus, two new matrilines for Liuixalus, and Polypedates leucomystax species complex. Intraspecific genetic distances ranged from 0.000 to 0.119 and interspecific genetic distances ranged from 0.015 to 0.334. Within Rhacophorus and Kurixalus, the intra- and interspecific genetic distances did not reveal an obvious barcode gap. Notwithstanding, we found that COI sequences unambiguously identified rhacophorid species and helped to discover likely new cryptic species via the synthesis of genealogical relationships and divergence patterns. Our results supported that COI is an effective DNA barcoding marker for Rhacophoridae.